Remote sources of water vapor forming precipitation on the Norwegian west coast at 60o N - a tale of hurricanes and an atmospheric river - Stohl, Andreas; Forster, Caroline; Sodemann, Harald (Journal of Geophysical Research: Atmospheres, 2008)
In September 2005, an extreme precipitation event occurred on the Norwegian southwest coast, which produced flooding and landslides and caused considerable infrastructure damage and loss of human life. We found that this event was triggered by the transport of tropical and subtropical moisture associated with two former hurricanes, Maria and Nate, which both underwent transition into extratropical cyclones. The two former hurricanes generated a large stream of (sub)tropical air which extended over more than 40° of latitude and across the North Atlantic Ocean and carried a large amount of moisture originally associated with hurricane Nate; a so-called atmospheric river or moisture conveyor belt. The mountains along the Norwegian coast caused a strong orographic enhancement of the precipitation associated with the moist air. A Lagrangian moisture tracking algorithm was employed to show that the evaporative source of the precipitation falling over Norway was distributed over large parts of the North Atlantic Ocean, and indeed included large contribution from the subtropics and smaller ones from the tropics. The moisture tracking algorithm was also applied over a 5-year period. It was found that (sub)tropical sources can contribute substantially to the precipitation falling in southwestern Norway throughout the year. Thus other transport mechanisms than hurricanes are important, too, for moving (sub)tropical moisture so far north. The (sub)tropical moisture source is relatively more important during the positive phase of the North Atlantic Oscillation, as well as for stronger precipitation events.